1996
DOI: 10.1073/pnas.93.20.10826
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of myr 6, an unconventional myosin of the dilute/myosin-V family.

Abstract: We have isolated cDNAs encoding a second member of the dilute (myosin-V) unconventional myosin family in vertebrates, myr 6 (Myosin from rat 6). Expression of myr 6 transcripts in the brain is much more limited than is the expression of dilute, with highest levels observed in choroid plexus and components of the limbic system. We have mapped the myr 6 locus to mouse chromosome 18 using an interspecific backcross. The 3' portion of the myr 6 cDNA sequence from rat is nearly identical to that of a previously pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 38 publications
1
73
0
1
Order By: Relevance
“…6 MYO5B is a large gene (372 kb, 40 exons) encoding a multifunctional protein expressed in a variety of brain structures, including dendritic spines, at high levels. 39,40 Myosins are known to transport proteins in neurons through binding to their C-terminal globular domain, 41 and MYO5B specifically regulates vesicle trafficking. 42 Strikingly, MYO5B has been shown to regulate EGFR cycling in both canine (MDCK) and human cells (A431).…”
Section: Discussionmentioning
confidence: 99%
“…6 MYO5B is a large gene (372 kb, 40 exons) encoding a multifunctional protein expressed in a variety of brain structures, including dendritic spines, at high levels. 39,40 Myosins are known to transport proteins in neurons through binding to their C-terminal globular domain, 41 and MYO5B specifically regulates vesicle trafficking. 42 Strikingly, MYO5B has been shown to regulate EGFR cycling in both canine (MDCK) and human cells (A431).…”
Section: Discussionmentioning
confidence: 99%
“…It would be worthwhile to know what kind of functional relationship may exist between these neurochemical characteristics of the dorsal cochlear nuclei and the coincident MVa expression. Zhao et al (1996) demonstrated that another member of the myosin V class, the so-called myr 6 (myosin Vb), is specifically expressed in hippocampus, choroids plexus and amygdala of normal rats. Consequently, this paralogue may be a candidate to probe for the participation of brain myosins in temporal lobe hyperexcitable networks.…”
Section: Discussionmentioning
confidence: 99%
“…There are three myosin V family members in mammals (Mercer et al, 1991;Zhao et al, 1996;Rodriguez and Cheney, 2002) that have been implicated in genetic diseases and membrane trafficking (Mooseker and Cheney, 1995;Hasson and Mooseker, 1996;Titus, 1997). A role for myosin Vb in endocytic trafficking, specifically at a recycling step (Lapierre et al, 2001;Volpicelli et al, 2002), has been suggested based on the ability of the myosin Vb tail domain to retard recycling of the M4 muscarinic acetylcholine receptor (Volpicelli et al, 2002) and the Tf receptor (Lapierre et al, 2001) and to result in the accumulation of Tf in pericentriolar vesicles (but see Provance et al, 2004).…”
Section: Discussionmentioning
confidence: 99%